Viewing low back pain through the lens of spinal evolution: Understanding the morphology and limits of the human spine - Abdullah Emre Taçyıldız; Özden Erhan Sofuoğlu; Aydın Sinan Apaydın; Melih Üçer (PLoS ONE, 2026)
Background and objective Low back pain remains a pervasive global health challenge, with significant disability and socio-economic burden. While contemporary biomechanical and occupational factors are well-studied, the role of human spinal evolution and its divergence from modern postural behaviors is less frequently examined. This study aims to visually explore and illustrate the historical evolution of human spinal posture through artistic representations, conceptually highlighting the potential biomechanical mismatch between our spine’s evolutionary adaptations and current lifestyle-driven postures. Methods We conducted a qualitative visual analysis of human figures depicted in selected artworks from three distinct historical periods: the hunter-gatherer era, the agricultural transition, and the post-industrial age. Observed spinal postures were qualitatively compared to established biomechanical data on intradiscal pressure levels, derived from previous in-vivo studies. This comparison was used to illustrate potential physiological or pathological loading on the spine across different historical contexts. Results Our visual observations suggest a noticeable shift in depicted human postures over time. Figures from the hunter-gatherer period primarily exhibit upright, dynamic positions with an apparent absence of prolonged sitting or significant forward flexion. In contrast, artworks from agricultural and post-industrial societies frequently portray individuals in more flexed, static, and often ergonomically suboptimal postures, including prolonged sitting, bending, and heavy lifting with improper form. These observed postural trends visually align with positions independently associated with increased intradiscal pressures and greater spinal strain in biomechanical literature. Conclusion This study visually traces the evolution of human spinal posture from the hunter-gatherer era to modern industrial life, highlighting a shift from dynamic, biomechanically healthy positions to static and suboptimal postures. These changes, reflected in historical art and linked to lifestyle transitions such as agriculture and industrialization, may underlie the rising prevalence of spinal disorders. The findings suggest that aligning modern practices with the spine’s evolutionary design could help prevent and manage spinal pathologies.